Remote education and teaching performance in educational institutions of Huancavelica in times of COVID-19 - Huamán Ramos, León (2021)
The objective of this study was to describe the performance of teachers at the secondary level of the district of Huancavelica-Peru, in the implementation of a remote education in times of the Covid-19 pandemic, digital and social-emotional behavior in a social situation of isolation. The study is of a qualitative nature, framed in the type of socio-critical interpretive paradigm research, designed through grounded theory methodology, with the application of the semi-structured interview in a sample of 4 teachers from the different curricular areas, 4 hierarchical teachers (managers and coordinators) and 6 students of the VII cycle of secondary education. The following conclusions were reached; (1) Teachers in these times of the Covid-19 pandemic have been facing complex moments of work, due to the drastic change from face-to-face education to remote education, which has a format very different from the traditional one, making use and management of resources technological, through synchronous and asynchronous work. (2). The teaching performance in these times of the Covid-19 pandemic refers to digital skills, which must be strengthened in the proper use and management of technological resources, and these difficulties have allowed teachers to make substantial changes in their behavior socio-emotional, frequently showing anxiety, loneliness, stress, sadness, worry, anger and negative thinking, as they require strengthening their socio-emotional adaptive capacity, to adequately face the challenges that the implementation of this new remote educational service modality.